The UNEJ KKN Program 'Smart Kids': Local Food Innovation In Stunting Mitigation Through Moringa And Soybean Husk (Glycine Max) Products: Program KKN UNEJ 'Smart Kids' : Inovasi Pangan Lokal Dalam Mitigasi Stunting Melalui Produk Kelor Dan Kulit Ari Kedelai (Glycine Max) (JURNAL UNEJ, 2024)
Stunting is one of the significant chronic nutritional issues in Indonesia, especially among young children. Data shows that although the prevalence of stunting has decreased, it remains high, including in Lumajang Regency, with a prevalence rate of 23.8%. Sawaran Lor village has local potential in the form of nutrient-rich moringa leaves, but their utilization has not been optimal. Another local potential, soybean hull waste from the tempeh industry, which is usually only used as animal feed, contains nutrients that can be utilized as functional food. The